2019
DOI: 10.1007/s12369-019-00583-2
|View full text |Cite
|
Sign up to set email alerts
|

Could Social Robots Make Us Kinder or Crueller to Humans and Animals?

Abstract: The Montréal Declaration for Responsible Development of Artificial Intelligence states that emerging technologies ought not "encourage cruel behaviour towards robots that take on the appearance of human beings or animals and act in a similar fashion." The idea of a causal link between cruelty and kindness to artiicial and living beings, human or animal, is controversial and underexplored, despite its increasing relevance to robotics. Kate Darling recently marshalled Immanuel Kant's argument-that cruelty to ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 64 publications
1
13
0
1
Order By: Relevance
“…Even if it were in some way irrational to worry about the wellbeing of a robot toy, we think it is worthwhile to consider the impact on the people who interact with the robots [36]. Indeed, some philosophers (following Kant) have proposed an analogous case in how the treatment of animals affects us.…”
Section: Is It Ok To Abuse a Cute Robot?mentioning
confidence: 99%
“…Even if it were in some way irrational to worry about the wellbeing of a robot toy, we think it is worthwhile to consider the impact on the people who interact with the robots [36]. Indeed, some philosophers (following Kant) have proposed an analogous case in how the treatment of animals affects us.…”
Section: Is It Ok To Abuse a Cute Robot?mentioning
confidence: 99%
“…Cappuccio et al [7] have argued for giving social robots moral consideration that is not based on intrinsic moral dignity and that does not attribute rights, but on the idea that relationships with robots offer to human agents opportunities to cultivate vices and virtues. And in this journal Coghlan et al [16] have reported that social robots, for example robots in the shape of animals, may affect virtue in terms of effects on the moral development of children and responses to nonhuman animals. Earlier I have discussed virtue and the good life in relation to care robots [12] and environmental technologies [10].…”
Section: Are Social Robots Kantian Dogs? Using Virtue Ethics For Thinmentioning
confidence: 99%
“…In the current virtue ethics of robotics literature, such relational elements are certainly present, but much more work is needed to develop this dimension of virtue and its relation to technology. For example, while Vallor [34] defines human beings as relational beings 'whose identity is formed through a network of relationships' [34,16] and discusses care practices (226), a systematic account of the role of practice viz-à-viz technomoral virtues and of the link between virtue and practices are missing. The latter can be found for instance in the work of MacIntyre (see below), but this corpus is not engaged with.…”
Section: Are Social Robots Kantian Dogs? Using Virtue Ethics For Thinmentioning
confidence: 99%
“…Robottien pahoinpitelijöiden moraalinen kauhistelu kuitenkin peittää todellisen moraalisen ongelman. Sen sijaan, että oltaisiin huolissaan robottien puolesta, olisi asiaankuuluvampaa olla huolissaan niiden kanssa vuorovaikutuksessa olevien ihmisten puolesta (Coghlan, Vetere, Waycott, & Barbosa Neves, 2019). On täysin mahdollista, että robottien ihmistämisestä johtuen niiden raaka kohtelu voi luoda ympäristön, jossa niiden kanssa vuorovaikutuksessa olevat ihmiset kehittävät moraalisia paheita.…”
Section: Saako Söpöä Robottia Pahoinpidellä?unclassified